How do you find #lim (1-t/(t-1))/(1-sqrtt/(t-1))# as #t->oo# using l'Hospital's Rule?

Answer 1

#0#

# (1-t/(t-1))/(1-sqrtt/(t-1)) = -1/(t-1-sqrtt) =-1/sqrtt(1/(sqrt t-1/sqrtt-1))#

then

#lim_(t->oo)(1-t/(t-1))/(1-sqrtt/(t-1)) = lim_(t->oo)-1/sqrtt(1/(sqrt t-1/sqrtt-1)) = 0#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the limit of the expression (1 - t/(t - 1)) / (1 - sqrt(t)/(t - 1)) as t approaches infinity using L'Hospital's Rule:

  1. Rewrite the expression as lim t->∞ (1 - t/(t - 1)) / (1 - sqrt(t)/(t - 1)).
  2. Since both the numerator and denominator approach infinity as t approaches infinity, apply L'Hospital's Rule by taking the derivative of the numerator and the derivative of the denominator separately.
  3. Take the derivative of the numerator: d/dt (1 - t/(t - 1)) = d/dt (1 - 1 + 1/(t - 1)) = d/dt (1/(t - 1)).
  4. Take the derivative of the denominator: d/dt (1 - sqrt(t)/(t - 1)) = d/dt (1 - t^(-1/2)/(t - 1)) = d/dt (1 - (t^(-1/2))/(t - 1)).
  5. Apply L'Hospital's Rule again if necessary until you reach a determinable limit or a form that can be simplified easily.
  6. Evaluate the limit of the derivatives as t approaches infinity.
  7. The result is the limit of the original expression as t approaches infinity.
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find ( \lim_{t \to \infty} \frac{1 - \frac{t}{t-1}}{1 - \frac{\sqrt{t}}{t-1}} ) using L'Hôpital's Rule, we apply the rule to the indeterminate form ( \frac{0}{0} ).

First, we differentiate the numerator and denominator separately with respect to ( t ):

[ \lim_{t \to \infty} \frac{d}{dt} \left(1 - \frac{t}{t-1}\right) \div \frac{d}{dt} \left(1 - \frac{\sqrt{t}}{t-1}\right) ]

[ = \lim_{t \to \infty} \frac{d}{dt} \left(1 - \frac{t}{t-1}\right) \div \frac{d}{dt} \left(1 - \frac{\sqrt{t}}{t-1}\right) ]

[ = \lim_{t \to \infty} \frac{0 - (t-1)(-1) - (-t)(t-1)^{-2}}{0 - (t-1)^{-\frac{3}{2}} - (-\frac{1}{2}t^{-\frac{1}{2}})(t-1)^{-1}} ]

[ = \lim_{t \to \infty} \frac{(t-1) - (t-1)^{-2}t}{(t-1)^{-\frac{3}{2}} + \frac{1}{2}t^{-\frac{1}{2}}(t-1)^{-1}} ]

[ = \lim_{t \to \infty} \frac{(t-1)^2 - t}{(t-1)^{-\frac{3}{2}} + \frac{1}{2}(t-1)^{-\frac{3}{2}}} ]

[ = \lim_{t \to \infty} \frac{t^2 - 2t + 1 - t}{(t-1)^{-\frac{3}{2}} + \frac{1}{2}(t-1)^{-\frac{3}{2}}} ]

[ = \lim_{t \to \infty} \frac{t^2 - 3t + 1}{(t-1)^{-\frac{3}{2}} + \frac{1}{2}(t-1)^{-\frac{3}{2}}} ]

Now, as ( t \to \infty ), the denominator ( (t-1)^{-\frac{3}{2}} + \frac{1}{2}(t-1)^{-\frac{3}{2}} ) approaches ( 0 ), and the numerator ( t^2 - 3t + 1 ) grows without bound. Therefore, the limit is of the form ( \frac{\infty}{0} ), which is an indeterminate form. So, we can apply L'Hôpital's Rule again.

Differentiate the numerator and denominator separately:

[ = \lim_{t \to \infty} \frac{d}{dt} (t^2 - 3t + 1) \div \frac{d}{dt} \left((t-1)^{-\frac{3}{2}} + \frac{1}{2}(t-1)^{-\frac{3}{2}}\right) ]

[ = \lim_{t \to \infty} \frac{2t - 3}{-\frac{3}{2}(t-1)^{-\frac{5}{2}} - \frac{3}{4}(t-1)^{-\frac{5}{2}}} ]

[ = \lim_{t \to \infty} \frac{2t - 3}{-\frac{3}{2}(t-1)^{-\frac{5}{2}} - \frac{3}{4}(t-1)^{-\frac{5}{2}}} ]

[ = \lim_{t \to \infty} \frac{2t - 3}{-\frac{9}{4}(t-1)^{-\frac{5}{2}}} ]

[ = \lim_{t \to \infty} -\frac{8}{9} \cdot (t-1)^{\frac{5}{2}} ]

Now, as ( t \to \infty ), ( (t-1)^{\frac{5}{2}} ) also goes to ( \infty ), but with a negative sign. So, the limit of ( -\frac{8}{9} \cdot (t-1)^{\frac{5}{2}} ) is ( -\infty ).

Therefore, the limit ( \lim_{t \to \infty} \frac{1 - \frac{t}{t-1}}{1 - \frac{\sqrt{t}}{t-1}} ) is ( -\infty ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7